Wear Investigation of Aluminum Alloy Surface Layers Fabricated through Friction Stir Welding Method - S. Vijayakumar; S. Anitha; R. Arivazhagan; Ashebir Dingeto Hailu; T. V. Janardhana Rao; Hari Prasadarao Pydi (Advances in Materials Science and Engineering)
In this research paper, an effort was made to investigate the dry sliding wear rate of friction stir welded AA6262/AA5456 composite performed by the Taguchi approach. Wear experiments are carried out by selecting suitable process parameters such as load (LD), sliding speed (SS), and sliding distance (SE) to recognize the individual and combination effects of parameters. Orthogonal array L27 mode is applied to make numbers of experiments to find the extreme and minimum wear amount. The experimental works are conducted on Pin on Disc (POD) apparatus and measured the weight of samples before and after test for calculating wear rate (WR) and then various analyses are performed such as ANOVA, interaction plot between parameters, and regression model with support of MINITAB software. The results revealed that maximum wear rate is found as 0.01215 mm3/Nm at LD of 50 N, SE of 600 m, and SS of 4 m/s, whereas minimum 0.00414 mm3/Nm at the grouping process parameters which are LD of 30 N, SE of 400 m, and SS of 6 m/s. From the observation of ANOVA, the most significant factor is identified as load, followed by sliding distance, sliding speed, and combination of each parameter. The load is considered as main parameter which contributes about 83.75% to achieve the maximum wear rate of developed AA6262/5456 composites. The contribution of sliding distance and speed are 3.75% and 1.85%, respectively.